If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + x + 2x + 3(2x) = 59 Remove parenthesis around (2x) y + x + 2x + 3 * 2x = 59 Multiply 3 * 2 y + x + 2x + 6x = 59 Reorder the terms: x + 2x + 6x + y = 59 Combine like terms: x + 2x = 3x 3x + 6x + y = 59 Combine like terms: 3x + 6x = 9x 9x + y = 59 Solving 9x + y = 59 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 9x + y + -1y = 59 + -1y Combine like terms: y + -1y = 0 9x + 0 = 59 + -1y 9x = 59 + -1y Divide each side by '9'. x = 6.555555556 + -0.1111111111y Simplifying x = 6.555555556 + -0.1111111111y
| 4x=-8x-60 | | -35-5n=-4(1+3n)-3 | | -4y+3z=-34 | | X^2-14y^2=0 | | m+n-4=n | | -9+7+3x-2=4x-2x | | 22-5x=16x | | 8x^2-8x+12=0 | | -x=6+x+2 | | 5x-3=8+5y | | y+2+3y=9 | | 7(7x+8)+9=49x+65 | | 200m-100m+52800=56100-175m | | 47=6x-2 | | -15+40=6x-70 | | 200m-100m+52800=56100-175 | | 49.3x^2+33.33x-62.9=0 | | -m+16=-4(2m-4) | | 5x+3y=5.50 | | 6x+11+37+72=180 | | -3-x=-3x+x | | 6x=1+3x-1 | | 8(4s+12)=8(3s-14) | | 5-(4x^2+9x)=0 | | -4.5+n=-5 | | x+(x+2)=5 | | -10+8x=1-3x | | -3(x+5)=-2x-23 | | 6+8+x=20 | | n=160(1-.4) | | 175m-75m+52250=56375-175m | | 4m-(-m)=6-m |